Peran Lembaga Keuangan Mikro Syariah (LKMS) dan Keberlanjutan Ekonomi Kreatif di Era Digital di Jawa Barat - Mariyah Ulfah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the role of Islamic Microfinance Institutions (LKMS) in sustaining the creative economy in West Java by incorporating digital adoption as a mediating variable and policy as a moderating variable. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM–PLS) was employed, based on survey data from 220 micro and small enterprises in culinary, fashion, and craft subsectors. The findings reveal that LKMS significantly influence both digital adoption and creative economy sustainability, directly and indirectly. Digital adoption serves as a key factor enhancing business sustainability, while policy strengthens the effect of LKMS on digital adoption, though only marginally on sustainability. The R² values of 0.31 for digital adoption and 0.56 for creative economy sustainability indicate moderate to strong explanatory power of the model. These results highlight the importance of integrating Islamic financing, business mentoring, and digitalization as a comprehensive strategy to ensure the sustainability of creative micro-enterprises at the regional level. This study contributes to the literature on Islamic microfinance and creative economy, while offering practical implications for policy and strengthening the role of LKMS.